Female Religious Authority in IMM; Phenomenological Study in Tarakan - Nur Hanida; Purwidianto (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This journal discusses religious authority for women in IMM. The phenomenon where in a religious group or organization still has the idea that women are not worthy or inappropriate to be dreamers or lead a religious activity even in ordinary people still think that women are only housewives who take care of their husbands, children and homes. This is a picture of the tradition of Islamic thought that is still rigid and undeveloped, thus impacting the social behavior of the immoderate community. so that this journal will discuss religious authority for women, especially in the Muhammadiyah Student Association as a forum for educating Islam-based student cadres and also has a special field regarding women or known as the IMMAWATI field, Therefore, it is interesting to know how religious authority for women in IMM, whether there is still a gender gap between men and women, and what are the problems experienced in applying authority in religion for women in IMM. The method used in this study is a qualitative method where this method is carried out by interviewing IMM members who have been active in IMM organizations as data that will be used as a reference to find out how religious authority for women in IMM.